Food hygiene practice and its associated factors among street food vendors in selected food vending locations in Bauchi Metropolis, Nigeria - Yahaya, Farida (2018)
Street food vendors (SFVs) contribute immensely in providing relatively nutritious food and livelihoods to many people in developing countries. However, there is a growing concern over the safety of the foods, particularly considering the vendors’ characteristics and operational mode. This study evaluated the food hygiene practice and its associated factors among SFVs in selected food vending locations in Bauchi metropolis, Nigeria. A cross-sectional study was performed on samples of 300 SFVs operating in selected food vending locations in Bauchi metropolis, which were selected and interviewed face to face from May to June, 2016. The data was collected using pre-tested structured questionnaire, containing four sections: SFVs’ characteristics, knowledge regarding food hygiene, attitude towards food hygiene and food hygiene practices. Statistical Software for Social Sciences (SPSS) version 21 was used throughout data analyses in this study. Both descriptive (frequencies, percentages, mean, standard deviation) and inferential statistics (chi-square and logistic regression) were employed to achieve robust results. Out of 300 SFVs that participated in this study, 174 (58.0%) are females, average aged 31±6.68 years, mainly characterized with low level of education 277 (92.3%), nonattendance of food hygiene training 244 (81.3%), and uncertified food businesses 246 (82.0%). Most of them 175 (58.30%) have poor level of knowledge regarding food hygiene, 189 (63.0%) have good level of attitude towards food hygiene and 151 (50.3%) have poor level of food hygiene practice. The chi-square test revealed that certain SFV’s characteristics including gender (X² = 10.094, p<0.05), education (X² = 8.147, p<0.05), experience (X² = 9.071, p<0.05), food hygiene training (X² =23.011, p<0.05), level of food hygiene knowledge (X² = 42.754, p = 0.001) and attitude towards food hygiene (X² = 16.785, p = 0.001) are associated with the level of food hygiene practice. From multiple logistic regression model as well, gender (AOR = 1.935, 95%CI = 1.129-3.317, p<0.05), experience (AOR = 2.537, 95%CI = 1.270-5.070, p<0.05), training (AOR = 3.649, 95%CI = 1.542-8.636, p<0.05), knowledge (AOR = 3.487, 95%CI = 1.976-6.154, p<0.05) and attitude towards food hygiene (AOR = 2.386, 95%CI = 1.371-4.153, p<0.05) are the factors predicting good food hygiene practice among SFVs.These findings showed that only less than half of the SFVs have good food hygiene practices, therefore it is recommended that relevant stakeholders should put much emphasis on all possible means for improving food hygiene practices among the SFVs which eventually safeguards the quality of the vended food. This should be done while taking into cognisance the factors found to be associated with food hygiene practice among the surveyed SFVs.